PEMBELAJARAN MATERI BANGUN RUANG MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER DI KELAS V SD - ., Yuri Irawadi (Jurnal Pembelajaran Prospektif, 2017)
The study was conducted based on several empirical evidences: (1) low students’ participation, this wass found when the teacher provided an opportunity to ask or answer, (2) none of the students asked or answered; (3) students were less serious in doing the task given; and (4) somestudents did not collect assignments at a given time. The purpose of this study was to describe the condition of learning mathematics, describe the form of RPP on building materials space and describe the implementation of model numbered heads together learning on the material of building room design in SDN 08 Sabung Setangga. The model of numbered heads together learning was one type of the cooperative learnings. Its typical characteristics was to assigna number to each group member and then simply appointed a student representing his group  by mentioning the students’ number, without notifying in advance who represented the group  aiming to all students’ readiness. The conclusion obtained that using the model numbered heads together learning made the students more active on the explanation delivered by theteacher, and provided the same perception of the learning.